Modelagem geométrica como mediadora da construção do conhecimento em desenho técnico no curso de edificações do IFBA, campus Salvador - Costa, Jefferson dos Santos (2017)
The decline of the teaching of the design subjects is expressed in the high repetition rates of students who study Technical design in the courses offered by the Instituto Federal da Bahia (IFBA). The fact that disciplines such as Geometric Design and Descriptive Geometry do not appear as compulsory in the curriculum as well as are not required in college entrance examinations makes them less important than Portuguese or Mathematics, for example. In this regard, the constructions of the motor aspects and the three-dimensional perceptual abilities of students are not seen as significant factors. This issue allows students to reach the first year of high school without the necessary basis to study design. This fact aims to demand a greater commitment of Design teachers to students who understand the subjects addressed. Based on this situation, computational programs focused on geometric design and modeling may have a pedagogical role in the development of spatial visualization skills, however, in the state of Bahia, undergraduate programs which train design teachers have not yet reformulated their résumés to include the teaching of new tools for these areas of knowledge. In order to contribute to the learning of the technical design, in the Building Technician course at IFBA, located in Salvador city, the present master's dissertation sought, through the tools of Geometric Modeling, a method that could contribute to the learning of the Technical Design.